Good Arts, Good Mental Health®: the effectiveness of an Australian health promotion media campaign in promoting community mental wellbeing via the arts - Davies, Christina R.; Pescud, Melanie T.; Clifford, Rhonda; McGrath, Richard; Thomson, Annie; Jeffrey, Mia; Stoneham, Melissa; Pikora, Terri; Wright, Peter; Girdler, Sonya; Baldassar, Loretta; Clift, Stephen (Frontiers in Public Health, 2025)
IntroductionThis study describes and evaluates Good Arts, Good Mental Health® (GAGMH), a groundbreaking, population-level, arts-mental health promotion media campaign. The objectives of the campaign (Wave 1) were to increase brand awareness, comprehension, and agreement with the tagline Good Arts, Good Mental Health® and empower the general population to form an intention to engage in the Arts for their mental wellbeing.MethodsThe campaign ran from August to September 2024 (4 weeks), cost AUD$198,965 (23% creative and 77% media/advertising distribution), and targeted the Western Australian (WA) general population aged 18–65 years, all genders, in both metropolitan and regional areas. The campaign was distributed through a variety of platforms, channels, visual, audio, and static assets. To gauge the success of the campaign, a process evaluation and (short-term) outcome evaluation were conducted by sourcing online analytics and conducting an online survey of the campaign target group (n = 661).ResultsOverall, campaign reach and frequency were optimal and met set targets. Campaign website engagement substantially increased from baseline (7,505 to 53,810 events 1 month after the campaign). Advertising cost-per-reach was effective and ranged from $0 for free/organic media to $0.10 for radio. For paid media channels, the highest reach (948,106 people) and best cost-per-reach ($0.02) were delivered by Meta (Facebook and Instagram).Measured as both (1) a proportion of total respondents and (2) a sub-set analysis of each preceding level in the cognitive impact hierarchy, post-campaign, one-in-four respondents were aware of Good Arts, Good Mental Health®. This is comparatively high for a new tagline and health campaign without TV advertising. Overall, comprehension was satisfactory. Agreement and intention to act on the message were high and double that of comparison Western Australian health promotion campaigns.DiscussionStudy findings indicate the GAGMH campaign was successful. If funded, future waves of the campaign could build on Wave 1 to reinforce message awareness, increase understanding of GAGMH concepts, focus more on the arts-mental health dose, and extend the outcome evaluation by measuring behavioral action. The information contained in this study is useful to Public Health, Mental Health, and Arts-Health professionals in the planning, implementation, and evaluation of future arts-mental health promotion strategies and campaigns.